EMOTION COACHING OLEH IBU PADA ANAK PRASEKOLAH - Wandansari, Yettie (EXPERIENTIA : Jurnal Psikologi Indonesia, 2020)
Early childhood is known as a critical period in the human life span. For this reason, optimization of early childhood development needs to be done in all aspects, including emotional aspects. In the preschool period, children's emotional development develops rapidly, namely in emotion knowledge, emotion expression, and emotion regulation. Parents, especially mothers, play an important role in child’s emotional development, one of which is through emotion coaching. According to the parental meta-emotion theory, emotion coaching includes parents' awareness of their own emotions and children's emotions. Parents who apply emotion coaching perceive children's negative emotions as important, are sensitive to children's emotional conditions, respect children's emotions, and use emotional situations constructively. In the process of interaction between parents and children, parents' reactions cannot be separated from the influence of their cultural values. However, research on emotion coaching by parents in the Indonesian context is still limited. Therefore, this study aims to obtain an overview of emotion coaching for mothers in Surabaya who have preschool aged children. Subjects were 147 mothers of children aged 3-6 years who attend Playgroup/ Kindergarten. The results showed that the majority of mothers (92%) showed a low level of emotion coaching. The discussion is related to the cultural framework. The results of the research can be further developed, for example exploring the cultural values of each ethnicity that contribute to emotion coaching, building models or emotion coaching interventions that are appropriate to the cultural context for parents in Indonesia.